Association between family economic hardship and university students' risky alcohol use: Mediating and moderating roles of perceived discrimination and impulsivity. (15th April 2019) - Zhu, Jianjun; Chen, Yuanyuan; Zhang, Wei
Abstract: Few studies have examined factors that might explain or affect the relation between family economic hardship and university students' risky alcohol use. To address this, the current study tested a moderated mediation model with perceived discrimination as the mediator and impulsivity as the moderator. A sample of 513 university students (48.6% males, 17–22 years old) completed anonymous questionnaires regarding family economic hardship, perceived discrimination, impulsivity and risky alcohol use. Gender, age and parents' education level were controlled for in the analyses. Structural equation models showed that perceived discrimination fully mediated the association between family economic hardship and risky alcohol use. Meanwhile, impulsivity moderated the second stage of the indirect effect (perceived discrimination → risky alcohol use); the association between perceived discrimination and risky alcohol use was only significant for university students with a higher (not lower) level of impulsivity. The findings suggest that perceived discrimination is one mechanism by which family economic hardship may be associated with university students' risky alcohol use, and impulsivity affects this mechanism.